General equilibrium impact evaluation of food top-up induced by households' renewable power self-supply in 141 regions. (15th January 2022) - Binh Nguyen, Duong; Nong, Duy; Simshauser, Paul; Nguyen-Huy, Thong
Highlights: Outputs of electricity and fossil fuel mining sectors decrease in all countries. Positive impacts on agriculture and food production occurs in all countries. Land prices increase significantly in land-scarce countries. Real GDP reduces in countries with less dependence on agriculture. GHG emission levels marginally reduce in various countries. Abstract: This article employs a global computable general equilibrium economic model (GTAP-E-PowerS) to examine the impact on the world economy if households in every country self-supply power to meet 30–100% of residential demand, with subsequent monetary savings diverted to consuming more food. Results show the power generation sector reduces output levels by 14%–42% across various countries if households 100% self-supply. Coal mining sectors are adversely affected in numerous countries with contractions of 9%–28% ($6, 086-$18, 935 million) in the United States and 4%–13% ($2, 505–$8, 143 million) in Australia. Improved outcomes for the world environment are found with reductions of CO2 e emission levels of 2.24%–7.38% (or 924–3, 042 MtCO2 equivalent). The agriculture and food-processing sectors expand significantly in many countries but also cause major increases in land prices, particularly in land-scarce countries in Middle East, Europe, Japan, and Taiwan. Results also show the security of food and energy supply are improved along with environmental gains from lower emission levels. However, the energy sector is adversely affected and those countries with a heavy reliance on fossil fuel extraction and mining activities experience significant reductions in real GDP.